1978
DOI: 10.2307/3279768
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of the Growth Factor Produced by Spirometra mansonoides and Growth Hormone in Diabetic-Hypophysectomized Rats: Lipid Composition

Abstract: The effects of bovine growth hormone and the growth factor produced by plerocercoid larvae of the tapeworm, Spirometra mansonoides, on body growth and lipid composition in diabetic-hypophysectomized rats were compared. The diabetic-hypophysectomized control rats gradually lost weight throughout the experiment but both growth hormone and plerocercoids stimulated marked weight gains. Growth hormone treatment resulted in a loss of depot fat from the epididymal fat pads and caused a reduction of liver and serum ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Most of the work on the growth-promoting (2, 4, 7,9,19) and metabolic effects (2, 8, 9,15,20) of PGF has been accomplished with chronic infections with plerocercoids. The acute effects of purified PGF on intermediary metabolism in mammals has not been reported.…”
mentioning
confidence: 99%
“…Most of the work on the growth-promoting (2, 4, 7,9,19) and metabolic effects (2, 8, 9,15,20) of PGF has been accomplished with chronic infections with plerocercoids. The acute effects of purified PGF on intermediary metabolism in mammals has not been reported.…”
mentioning
confidence: 99%
“…MEYER et al (1965) showed that plerocercoid-infected hamsters had a significant increased in carcass fat compared to uninfected controls. We (PHARES & CARROLL, 1978) found that plerocercoid infection of hamsters resulted in increase fat pad weights, serum total lipid, cholesterol and triglycerides.…”
Section: Introductionmentioning
confidence: 77%
“…Previous work shows that plerocercoid infection stimulates growth and increases fat stores in the absence of the pituitary (STEELMAN et al, 1971) and in the absence of normal insulin levels (PHARES & CARROLL, 1978). It has also been demonstrated that plerocercoid infection causes an increase in carcass fat (MEYER et al, 1965) and increases in serum triglycerides and cholesterol (PHARES & CARROLL, 1977) of intact hamsters.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, not all of the biological actions of plerocercoid growth factor (PGF) are similar to those reported for growth hormone (GH) HARLOW et ai (1967) reported insulin-like activity in extracts of plerocercoids in vitro. In addition, a distinct lipogenic effect of plerocercoid infection was reported in hypophysectomized (Hx) rats (STEELMAN et a!., 1971), Hx-diabetic rats (PHARES & CARROLL, 1978) and intact hamsters (PHARES & CARROLL, 1977). This chronic lipogenic effect of PGF is "insulin-like" as opposed to the lipolytic effect of chronic administration of GH (KNOBIL & HOTCHKISS, 1964).…”
Section: Ntroductionmentioning
confidence: 99%